A análise dos critérios de efetividade da governança de TI em organizações tecnológicas: o caso de uma empresa do setor de telecomunicações - Sortica, Eduardo Almansa (2008)
This study attempted to understand the relationship between strategic and tactical/operational IT governance effectiveness criteria for the formulation and implementation of strategies in a telecommunications services company. In order to achieve that, first it was checked if tactical/operational effectiveness criteria were seen and used by the organization, following any framework of technological governance. Then, the existence of strategic effectiveness criteria was also checked, based on definitions in the literature and the work of other researchers. At last, the relative importance of such criteria was evaluated, for the definition and implementation of the organization’s strategy. The case study involved interviews with several executives, using a predefined script. After the analysis of the data, it was concluded that all tactical/operational effectiveness criteria included in the studied categories were implemented. Some categories of strategic effectiveness criteria were detected, while other was missing. Four categories of operational criteria and two of strategic criteria were thoroughly implemented and had significant importance for the studied organization. The limitations of the study involve the fact that the researcher did not have direct access to the methodology that was borrowed from Gartner Group, which was obtained in a third study. In addition to that, the analysis of the data provided by the respondents ended up being biased by their technical profile. It is suggested that in future studies the same methodology is used, but aiming at top management professionals in telecommunications carriers or service companies that support the telecommunications sector.